Post-pandemic face-to-face learning: Perspectives from physical education teachers - Wahyu Ragil Kurniawan; Mugiyo Hartono; Dwi Gansar Santi Wijayanti (UIR Press, 2023)
Returning to the face-to-face learning system for physical education, the researchers got several responses and responses from the stakeholders, one of which was the teacher. The purpose of this study was to determine the perceptions of physical education teachers in carrying out face-to-face learning activities in the post-pandemic. The method used is descriptive quantitative research. Data collection was carried out using a list of main questions that were used to guide this research, one of which was,